ANALISIS PENGARUH FAKTOR FUNDAMENTAL TERHADAP HARGA SAHAM DENGAN ROA SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN LQ 45 PERIODE 2010-2013 - Dwisona, Shindy Widha; Haryanto, A. Mulyo (Diponegoro Journal of Management, 2015)
The aims of this research are to know : (1) The effect of Debt Ratio (DR), Working Capital to Total Assets (WC/TA), and Current Ratio (CR) to Return On Assets (ROA), (2) The effect of Debt Ratio (DR), Working Capital to Total Assets (WC/TA), Current Ratio (CR), and Return On Assets (ROA) to the stock price, (3) The effect of Debt Ratio (DR), Working Capital to Total Assets (WC/TA), and Current Ratio (CR) to the stock price through Return On Assets (ROA) as an intervening variable. The research samples are companies that included in the LQ 45 index in the period 2010-2013 by using purposive sampling method. There are 15 companies that meet the criteria as the sample. This research used path analysis which is the development of multiple regression analysis and bivariate.The result of this research showed that : DR has negative significant effect on ROA, WC/TA has positif effect on ROA but not significant, CR has negative significant effect on ROA, DR has negative significant effect on stock price, WC/TA has positive significant effect on stock price, CR has negative significant effect on stock price, ROA has positive significant effect on stock price. The result of sobel test showed that WC/TA and CR has indirectly effect on stock price through ROA.